When family language policy and early bilingualism research intersect: A case study - Verschik, Anna; Argus, Reili (Taikomoji kalbotyra, 2024)
The article discusses family language policy in a family of ethnic Russians in Estonia where the father speaks Russian, and the mother speaks Estonian. This is the case of internalization of Estonian among ethnic Russians, a novel phenomenon in the post-Soviet countries. The data come from family conversations (6 h) and the semi-structured interview with the parents (1.5 h). There are discrepancies between the declared ideologies, management, and practices. The declared policy is OPOL and, as the father rendered it, purism because of the concern that the children will be confused otherwise. During the interview the father switched between Estonian, Russian, and English. In family conversations the mother’s speech (539 turns, of which 50 % are directed to the child) contained code-switching (7% in Russian and 8% switches within one turn in speech directed to the child). The parents claimed to speak Russian to each other, yet the mother occasionally switched to Estonian while talking to the father. In general, both family conversations and the interview proved to be linguistically more diverse than expected.